4H–SiC floating junction Schottky barrier diode with compensation layer of engineered cathode structure: Cone-shaped electric field, current density waveform, and applications. (July 2022) - Nan, Yagong; Han, Genquan
Abstract: In order to further elevate its adaptability as a power device, the electrical properties of 4H–SiC floating-junction Schottky barrier diode with the compensation layer (CL) of engineered cathode structure were studied in this paper. The n-type CL was introduced near the cathode side of the device drift region, which can effectively compensate the transient recovery process, and alleviate the bipolar degradation of the unipolar device (RSF: 3.3589; trr : 1.0437 ns). The generation and transport mechanism of the current density suitable for static and dynamic performance was analyzed under the micron-meter-level condition. Some influencing factors, including the internal structure dimensions, the doping of CL, and temperature, were discussed quantitatively. The electric field distribution in the device was obtained according to Maxwell's theory ( ET : 3.50 × 10 6 V/cm). By embedding some p − -type layers in the upper part of drift region, the discharge output of p + -type-floating layer can be availably inhibited ( Qrr : 7.0260 × 10 –15 C/μm).